Post-synthesis modification of functionalised polyhedral oligomeric silsesquioxanes with encapsulated fluoride – enhancing reactivity of T8-F POSS for materials synthesis. (17th February 2021) - Laird, Mathilde; Gaveau, Philippe; Trens, Philippe; Carcel, Carole; Unno, Masafumi; Bartlett, John R.; Wong Chi Man, Michel
Abstract : The first successful approach for modifying poorly reactive POSS containing F − (T8 -F) and incorporating intact T8 -F within a nanohybrid material is described. Abstract : Previous studies have demonstrated that functionalised T8 polyhedral oligomeric silsesquioxanes with fluoride anions encapsulated within the T8 cage (T8 -F) have very low reactivity, with no reports of successful modification of the organic moieties. Herein, we report the successful modification of a styryl functionalised T8 -F compound with mercaptopropyltriethoxysilane using a thiol–ene click reaction. This strategy enables the vinyl moiety to be modified while maintaining the influence of the electron-withdrawing phenylene group, which stabilises the fluoride within the cage. The triethoxysilylated T8 -F cages were subsequently converted into nanohybrids by sol–gel processing. Multinuclear NMR experiments ( 29 Si, 19 F, 13 C) demonstrated that the POSS cage remained intact during both post functionalisation of T8 -F and subsequent sol-gel processing. Furthermore, 29 Si cross polarisation solid state NMR experiments using 19 F as a cross polarisation agent demonstrated that the fluoride anions remain localised within the cages in the nanohybrids. The functionalisation of the styryl bearing T8 -F POSS cage is the first example of both the successful modification of the poorly reactive T8 -F family and the formation of a nanohybrid material incorporating fluoride ions immobilised within covalently bound T8 cages.